Faktor-Faktor yang Memengaruhi Minat Berkarier sebagai Akuntan Bersertifikat Chartered Accountant (CA) - Sekar Ayu Pertiwi; I Gusti Ketut Agung Ulupui; Hera Khairunnisa (LPPM Universitas Negeri Jakarta, 2025)
This study aims to examine the effects of career exposure, self efficacy, financial rewards, work environment, social values, and job market considerations on students’ interest in pursuing a career as a Chartered Accountant (CA). This research employed a quantitative approach involving all undergraduate accounting students of the Faculty of Economics and Business, Universitas Negeri Jakarta (UNJ), class of 2022, with the entire population selected as the sample using a non-probability saturated sampling technique. Data were collected through a Likert-scale questionnaire ranging from 1 to 4 with items adapted from established indicators. The collected data were processed and analysed using the PLS-SEM approach with the SmartPLS software. The findings reveal that career exposure, financial rewards, and job market considerations have a positive and significant effect on career interest as a Chartered Accountant, while self efficacy, work environment, and social values do not show a significant influence.